2007
DOI: 10.1159/000108759
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Renal Tubulointerstitial Fibrosis by Small Interfering RNA Targeting Heat Shock Protein 47

Abstract: Background/Aim: Unilateral ureteral obstruction (UUO) is a well-established model for tubulointerstitial fibrosis. During the progression of tubulointerstitial fibrosis, upregulation of collagen synthesis and subsequent accumulation of collagen were observed in the tubulointerstitial area. Heat shock protein 47 (HSP47) is a collagen-specific molecular chaperone and plays an essential role in regulating collagen synthesis. We designed small interfering RNA (siRNA) sequences for HSP47 mRNA to examine whether HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 107 publications
2
45
0
Order By: Relevance
“…Immediately after right ureteral obstruction, 50 mL of SET7/9-siRNA solution (7 mg/kg) was injected retrogradely once into the right kidney via the ureter. 38,39 Sinefungin (Sigma-Aldrich, St Louis, MO) was prepared as a suspension in distilled water and 0.9% NaCl solution, and administered intraperitoneally (0.1 mL per mouse) at a dose of 10 mg/kg per day immediately after UUO. The control group was administered an equal volume of vehicle (0.1 mL of distilled water and 0.9% NaCl solution) intraperitoneally.…”
Section: Drug and Sirna Administration In Vivomentioning
confidence: 99%
“…Immediately after right ureteral obstruction, 50 mL of SET7/9-siRNA solution (7 mg/kg) was injected retrogradely once into the right kidney via the ureter. 38,39 Sinefungin (Sigma-Aldrich, St Louis, MO) was prepared as a suspension in distilled water and 0.9% NaCl solution, and administered intraperitoneally (0.1 mL per mouse) at a dose of 10 mg/kg per day immediately after UUO. The control group was administered an equal volume of vehicle (0.1 mL of distilled water and 0.9% NaCl solution) intraperitoneally.…”
Section: Drug and Sirna Administration In Vivomentioning
confidence: 99%
“…Such incorporated compounds have been reported to be released from the hydrogel after its degradation by endogenous enzymes secreted from the surrounding tissues (23). One week after the injection, the rats were sacrificed, both ears were removed, and 7-m-thick frozen sections were examined in an immunofluorescence study using the same concentrations of antibodies as those shown in the previous section.…”
Section: Identification Of Rclca-t and Generation Of Stable Expressiomentioning
confidence: 99%
“…S4). Transfection of an siRNA together with CGM has been reported to have a long-lasting effect on the expression of the target molecule (23). In control (scrambled RNA ϩ CGMtreated) skin, a confocal microscopic study showed that rCLCA-t displayed an intracellular localization.…”
Section: Rclca-t Decreases Integrin-dependent Cell Attachment In Respmentioning
confidence: 99%
“…These nanoparticles were shown to inhibit TBR expression and ameliorated fibrotic changes in the fibrotic kidney compared with naked plasmid DNA designed for the expression of TBR siRNA injection [52]. Heat shock protein 47 (HSP47) siRNA with cationized gelatin nanoparticles was shown to knock down HSP47 expression and diminish renal fibrosis in a mouse model of renal fibrosis induced by UUO [53]. Cationic gelatin nanoparticles incorporating plasmid DNA expressing matrix metalloprotease was shown to prevent renal fibrosis in a mouse model of diabetic nephropathy produced by intraperitoneal injection of streptozotocin, which causes damage to the pancreas and results in diabetic nephropathy [54,67].…”
Section: Viral and Non-viral Vectors For Renal Fibrosis In Vivomentioning
confidence: 99%